(untitled) (Revista de Ciências Agroveterinárias, 2025)
Similar to other species, lymph nodes are the primary metastatic site for mammary gland tumors in cats. Although lymphography is a useful tool for identifying regional and sentinel lymph nodes in oncology, it remains underused in veterinary medicine due to unawareness and financial restraints. Patent blue dye is the most commonly used vital dye for visualizing lymph nodes during surgery in dogs and cats. This study aimed to identify and describe the lymphatic drainage of mammary glands, axillary, and superficial inguinal lymph nodes in cats using 2.5% patent blue dye. The dye was administered post-mortem to specific mammary glands of 13 female cats. The lymph nodes were then examined for number, size, anatomic location, and macroscopic characteristics, and further evaluated through histopathology. The dye successfully marked the lymph nodes in 92.3% of cases (12 out of 13), staining 32 lymph nodes. Notable anatomical variations were observed, with 38.5% of cats presenting two axillary lymph nodes, and only one superficial inguinal lymph node identified per cat. Patent blue dye proved to be an efficient technique for locating lymph nodes involved in the lymphatic drainage of mammary glands in female cats.